The Pathology of Relational Aesthetics and the Anomaly of Adaptive Behavior of Transformation in Nuruddin Farah’s Crossbones (2011) - Souleymane Diallo (Borong Newinera Publisher, 2022)
The postmodernist material cause of the schema of Crossbones implies an innovative method and a meta-cognition realm within postcolonial system of proposition and metadata, involves a new approach of intellection in the perspective relational values and relational frame theory stand as a dimensionality of understanding and a generative and transformative reality. Through an object program and a normative functionalism, Farah installs a psycho-functionalist perspective in the run to transcend the realm of ethnocentrism and relegio-politico social theory concerning the domain of formal conception and perception of relationalism. This persistence relates to an alternative understanding, a modality and property differentiation concerning the relational aesthetic and the status quo of the Be-ing, and a transformative reform about human intellect prerequisites and requests. in this dynamic of social practice and evidence-based practice, the relational aesthetic theory within Farah evolves his docufiction, define a method of linguistic performance and a relational expression that focuses on a conceivable representation of truth and experience.